Design of Graduate Learning Outcome Management Features in INSPIRE OBE Application - Rivaldy Abraham Michael Tulung; Alwin Sambul; Sary Paturusi (Jurnal Teknik Elektro dan Komputer, 2026)
Abstract — Outcome-Based Education (OBE) positions Program Learning Outcomes (PLO/CPL) as the core reference for curriculum design, course planning, and assessment. In practice, study programs often struggle with maintaining consistent CPL data, mapping each CPL to supporting courses, and assigning contribution weights required for measurable attainment calculations. This study presents the design of a CPL management feature within the INSPIRE application at Universitas Sam Ratulangi to centralize CPL definition, link CPL items to relevant courses, and manage contribution weights in a traceable, well-documented manner. A prototype approach was employed so that interface designs and validation rules could be iteratively evaluated with key users (study program coordinators). The resulting design enables CPL input based on curriculum context, connects each CPL to a list of courses with defined contribution weights, and prepares a data structure that supports the OBE traceability chain down to Course Learning Outcomes (CPMK) and Sub-CPMK. The feature improves traceability between graduate targets and supporting courses, reduces reliance on scattered documents, and provides a reliable foundation for subsequent monitoring and evidence-based quality assurance. Keywords — OBE, learning outcomes, curriculum mapping, weighting, INSPIRE